Pulsed plasma chemical synthesis of carbon-containing titanium and silicon oxide based nanocomposite; Radiation Physics and Chemistry; Vol. 144 - Kholodnaya G. E. Galina Evgenievna; Sazonov R. V. Roman Vladimirovich; Ponomarev D. V. Denis Vladimirovich; Zhirkov I. S. Igor Sergeevich (2018, 2018)
Title screen